Le ‘maestre’ di Adelaide Ristori: tracce di una trasmissione generazionale del mestiere - Giulia Bravi (Drammaturgia)
This paper proposes a comparison between Adelaide Ristori and the actresses of the previous generation searching for traces of an unwritten transmission of the theatrical craft. The research focuses particularly on the relationship between Ristori and Carolina Internari, which is less investigated than the relationship with Carlotta Marchionni, recognized by Ristori as a real teacher. Internari plays with Ristori several times since 1852, supporting her in the interpretations of Mirra, Maria Stuarda and other ‘warhorses’ impacting the construction of some tragic heroines. The documents preserved in the Museo Biblioteca dell’Attore in Genoa, integrated with sources found in other documentary deposits, are the foundation of this historical analysis which recounts the human and artistic exchange between these great actresses in the 19th century.